Inhibition of A2A Adenosine Receptor Signaling in Cancer Cells Proliferation by the Novel Antagonist TP455 - Gessi, Stefania; Bencivenni, Serena; Battistello, Enrica; Vincenzi, Fabrizio; Colotta, Vittoria; Catarzi, Daniela; Varano, Flavia; Merighi, Stefania; Borea, Pier Andrea; Varani, Katia (Frontiers in Pharmacology, 2017)
Several evidence indicate that the ubiquitous nucleoside adenosine, acting through A1, A2A, A2B and A3 receptor (AR) subtypes, plays crucial roles in tumor development. Adenosine has contrasting effects on cell proliferation depending on the engagement of different receptor subtypes in various tumors. The involvement of A2AARs in human A375 melanoma, as well as in human A549 lung and rat MRMT1 breast carcinoma proliferation has been evaluated in view of the availability of a novel A2AAR antagonist, with high affinity and selectivity, named as 2-(2-furanyl)-N5-(2-methoxybenzyl)[1,3]thiazolo[5,4-d]pyrimidine-5,7-diammine (TP455). Specifically, the signalling pathways triggered in the cancer cells of different origin and the antagonist effect of TP455 were investigated. The A2AAR protein expression was evaluated through receptor binding assays. Furthermore, the effect of A2AAR activation on cell proliferation at 24, 48 and 72 hours was studied. The selective A2AAR agonist 2-p-(2-carboxyethyl)phenethylamino-5'-N-ethylcarboxamidoadenosine hydrochloride (CGS21680), concentration-dependently induced cell proliferation in A375, A549 and MRMT1 cancer cells and the effect was potently antagonized by the A2AAR antagonist TP455, as well as by the reference A2AAR blocker 4-(2-[7-amino-2-(2-furyl)[1,2,4]triazolo[2,3-a][1,3,5]triazin-5-ylamino]ethyl)phenol, (ZM241385). As for the signalling pathway recruited in this response we demonstrated that, by using the specific inhibitors of signal transduction pathways, the effect of A2AAR stimulation was induced through phospholipase C (PLC) and protein kinase C-delta (PKC-δ). In addition, we evaluated, through the AlphaScreen SureFire phospho(p) protein assay, the kinases enrolled by A2AAR to stimulate cell proliferation and we found the involvement of protein kinase B (AKT), extracellular regulated kinases (ERK1/2) and c-Jun N-terminal kinases (JNKs). Indeed, we demonstrated that the CGS21680 stimulatory effect on kinases was strongly reduced in the presence of the new potent compound TP455, as well as by ZM241385, confirming the role of the A2AAR. In conclusion, the A2AAR activation stimulates proliferation of A375, A549 and MRMT1 cancer cells and importantly TP455 reveals its capability to counteract this effect, suggesting selective A2AAR antagonists as potential new therapeutics.